Development of a Mini Compression Test Machine using Arduino Microcontroller as Texture Analyzer Prototype - Angelica, Putri; Yetti, Musafri; Triawan, Farid; Sutanto Hadisujoto, Ignatius Budi; Hamidah, Ida (Jurnal Otomasi Kontrol dan Instrumentasi, 2023)
A texture analyzer is a standard device to measure food texture properties. This study aims to develop a mini compression test machine prototype that can function as a texture analyzer with simple operation and portability. The components and materials were chosen based on: low cost, manufacturability, and availability in the local Indonesian market. The prototype dimension was 375 × 215 × 450 mm, and used a linear ball screw slider for the translation movement with a 200 mm effective sliding distance. For obtaining the compression load, a 10 kg load cell was used, and it was replaceable by a load cell with a lower capacity if a higher measurement accuracy was required. After calibration, the linear vertical displacement and load cell had ±0.1 mm and ±1 g of accuracy, respectively. The prototype was tested to measure the texture properties of potato chops. As a result, the machine could successfully measure the load and displacement data and detect a crack phenomenon, verifying its usability as a food texture analyzer.